Reappraisal of the chronology of Orgnac 3 Lower-to-Middle Paleolithic site (Ardèche, France), a regional key sequence for the Middle Pleistocene of southern France. Issue 162 (January 2022) - Bahain, Jean-Jacques; Mercier, Norbert; Valladas, Hélène; Falguères, Christophe; Masaoudi, Hassan; Joron, Jean-Louis; Froget, Laurence; Moigne, Anne-Marie; Combier, Jean; Moncel, Marie-Hélène
Abstract: Previous studies have suggested that the Lower-to-Middle Paleolithic transition was associated with the earliest Neanderthals, but recent research has established that the oldest Neanderthal fossils and the first signs of their technologies and behavior appear from MIS 11 or possibly earlier. To understand these changes, re-evaluation of the evidence is necessary to determine if this transition corresponds to a progressive evolution rather than abrupt change. Orgnac 3 is a key and appropriate site to study this research context. Located in southern France, it yields a long stratigraphic sequence testifying the evolution of technical and subsistence behaviors of pre-Neanderthal human groups during a Middle Pleistocene interglacial-glacial cycle. In this article, a new chronological framework is provided for the sequence based on results of dating methods applied to various types of geological materials. Speleothems and volcanic minerals, dated in previous studies by U-series and 40 Ar/ 39 Ar, respectively, show periods of calcitic crystallization and regional volcanic activity. Other materials, such as heated flints and herbivore teeth, are directly related to evidence of anthropogenic activities and are analyzed in the present work by trapped-charge dating methods such as thermoluminescence and electron spin resonance combined with uranium series (ESR/U-series). The new thermoluminescence and ESR/U-series dates confirm the attribution of the Orgnac 3 stratigraphic sequence to the MIS 10–MIS 8 period and are discussed in relation to paleoenvironmental data derived from bioarchaeological studies. The paleoanthropological levels, including the emergence of Levallois technology, are dated to ca. 275 ka (early MIS 8) and appear coeval to a wet and temperate period recorded locally, the Amargiers interstadial, defined in the regional palynological records. The implications of this reassessed chronology for the archaeological assemblages are discussed in the wider context of behavioral innovations from MIS 11 onward and their establishment in subsequent periods.